Delayed modulation of alpha band activity increases response inhibition deficits in adolescents with AD(H)D - Katharina Graf; Roula Jamous; Moritz Mückschel; Annet Bluschke; Christian Beste (NeuroImage: Clinical)
Deficiencies in inhibitory control are one of the hallmarks of attention-deficit-(hyperactivity) disorder (AD(H)D). Response inhibition demands can become increased through additional conflicts, namely when already integrated representations of perception–action associations have to be updated. Yet, the neural mechanisms of how such conflicts worsen response inhibition in AD(H)D are unknown, but, if identified, could help to better understand the complex nature of AD(H)D-associated impulsivity. We investigated both behavioral performance and EEG activity in the theta and alpha band of adolescents (10–18 years of age) with AD(H)D (n = 28) compared to neurotypical (NT) controls (n = 33) in a conflict-modulated Go/Nogo paradigm. We used multivariate pattern analysis (MVPA) and EEG-beamforming to examine how changes in representational content are coded by oscillatory activity and to delineate the cortical structures involved in it. The presented behavioral and neurophysiological data show that adolescents with AD(H)D are more strongly affected by increased response inhibition demands through additional conflicts than NT controls. Precisely, AD(H)D participants showed higher false alarm rates than NT controls in both, non-overlapping and overlapping Nogo trials, but performed even worse in the latter. This is likely due to an inefficient updating of representations related to delayed modulations of alpha band activity in the ventral stream and orbitofrontal regions. Theta band activity is also modulated by conflict but was not differentially affected in the two groups. By this, the present study provides novel insights into underlying neurophysiological mechanisms of the complex nature of response inhibition deficits in adolescents with AD(H)D, stressing the importance to examine the interplay of theta and alpha band activity more closely to better understand inhibitory control deficits in AD(H)D.